Diagnosis as a social and political practice - Morison T (Massey University, 2025)
In this chapter, we examine diagnosis not just as a process of labelling diseases, but as a practice that establishes a shared understanding of what constitutes sickness—an understanding shaped by values, norms, and biology, and imbued with significant social consequences (Jutel, 2024). We begin by asking, “What is diagnosis?”—exploring how naming and framing create diagnostic systems that often struggle with ambiguity. Next, we examine diagnosis as a social tool. In medical interactions, healthcare providers wield the “power to name,” raising questions: Who benefits from specific diagnoses? What role do they play in maintaining the status quo and, hence, social inequity? We also consider diagnosis in the context of medicalisation, whereby everyday experiences are reframed as medical issues through diagnostic classifications. We discuss the benefits, such as validation and care, and drawbacks, including stigma and oversimplification, associated with this practice.
Keywords: diagnosis; health psychology; power; medicalisation; contested illness; medically unexplained illness; illness